The Source of Uncertainty in 3D Laser Scanner - M. S., Kamil; A. M., Kamely; H. Y., Saifudin; A. P., Puvanasvaran; M.M.P., Dan (2010)
3D laser scanner become popular in manufacturing field because of its capability in measuring various characteristics of part and reverse engineering. It is found that laser scanner which categorize under non-contact method is less accurate compared to the contact method. This is due to the output quality that depending on digitizing points captured during scanning. These digitizing points are affected from extrinsic and intrinsic parameters. Some of the parameters for commercial lasers are already calibrated prior to delivery. In this paper, extrinsic parameters are discussed based on LC15 laser scanner with Metris scan 4.1 software. A suggestion on model of uncertainty is suggested based on propagation of uncertainty method align with the understanding of extrinsic scanning parameters.